WAWASAN SOSIOLOGIS: NAKAL NAMUN PERLU - Yohanes I Wayan Marianta (Litbang STFT Widya Sasana Malang, 2011)
This article intends to introduce lay readers to sociological perspectives. Exploring sociological perspectives is a troubling yet rewarding venture. Sociological perspectives stimulate critical questions that challenge people to examine many assumptions they have taken for granted in the course of their everyday lives. Exploring sociological perspectives begins with looking at the world as a socially constructed world reproduced by people in their interrelationships with others. Social world is sustained by social structures which influence and, to a certain extent, shape people’s awareness, choices and behaviors. This is not to say that social structures are immutable facts, exempt from the possibility of change. Reading sociological perspectives helps readers grasp the dynamic interplay between social structures and human agency which underpins the phenomena of social order and change. Sociology bears the badge of being “a trouble maker” for its aptitude to reveal things that are hidden, or sometimes repressed, in social life and perturbs the status quo and those who have benefited from it. Exploring sociological perspectives, however, is rewarding and even fulfilling for those who seek to comprehend society with deeper understanding. Such understanding, in turn, invites and empowers them to get involved in collaborative struggles to weave a better world.